Attenuation of the Infiltration of Angiotensin II Expressing CD3+ T-Cells and the Modulation of Nerve Growth Factor in Lumbar Dorsal Root Ganglia – A Possible Mechanism Underpinning Analgesia Produced by EMA300, An Angiotensin II Type 2 (AT2) Receptor Antagonist - Khan, Nemat; Muralidharan, Arjun; Smith, Maree T. (Frontiers in Molecular Neuroscience, 2017)
Recent preclinical and proof-of-concept clinical studies have shown promising analgesic efficacy of selective small molecule angiotensin II type 2 (AT2) receptor antagonists in the alleviation of peripheral neuropathic pain. However, their cellular and molecular mechanism of action requires further investigation. To address this issue, groups of adult male Sprague-Dawley rats with fully developed unilateral hindpaw hypersensitivity, following chronic constriction injury (CCI) of the sciatic nerve, received a single intraperitoneal bolus dose of the small molecule AT2 receptor antagonist, EMA300 (10 mg kg−1), or vehicle. At the time of peak EMA300-mediated analgesia (~1 h post-dosing), groups of CCI-rats administered either EMA300 or vehicle were euthanized. A separate group of rats that underwent sham surgery were also included. The lumbar (L4-L6) dorsal root ganglia (DRGs) were obtained from all experimental cohorts and processed for immunohistochemistry and western blot studies. In vehicle treated CCI-rats, there was a significant increase in the expression levels of angiotensin II (Ang II), but not the AT2 receptor, in the ipsilateral lumbar DRGs. The elevated levels of Ang II in the ipsilateral lumbar DRGs of CCI-rats were at least in part contributed by CD3+ T-cells, satellite glial cells (SGCs) and a subset of neurons. Our findings suggest that the analgesic effect of EMA300 in CCI-rats involves multimodal actions that appear to be mediated at least in part by a significant reduction in the otherwise increased expression levels of Ang II as well as the number of Ang II-expressing CD3+ T-cells in the ipsilateral lumbar DRGs of CCI-rats. Additionally, the acute anti-allodynic effects of EMA300 in CCI-rats were accompanied by rescue of the otherwise decreased expression of the mature nerve growth factor (NGF) in the ipsilateral lumbar DRGs of CCI-rats. In contrast, the increased expression levels of TrkA and glial fibrillary acidic protein in the ipsilateral lumbar DRGs of vehicle-treated CCI-rats were not attenuated by a single bolus dose of EMA300. Consistent with our previous findings, there was also a significant decrease in the augmented levels of the downstream mediators of Ang II/AT2 receptor signaling i.e. phosphorylated-p38 mitogen-activated protein kinase (MAPK) and phosphorylated-p44/p42 MAPK, in the ipsilateral lumbar DRGs.